Global Sport Leaders A Biographical Analysis of International Sport Management (Springer International Publishing, 2018)
This book analyses the careers, governance and management practices of some of the institutional sports leaders who have had the greatest impact on global sport in the 120 years since Baron Pierre de Coubertin revived the Olympic Games. Through their positions in major sports organisations, their influence, the examples they set, their successes and failures, and their ability to bring about change, these notable individuals controlled and continue to control the development of Olympic and international sport. The portraits included within this collection provide a critical analysis of these leaders' careers by examining sports management from a biographical perspective, and allowing readers to understand the challenges and obstacles faced by international sport's top administrators. The contributors explore the interactions between these leaders' career paths and their strategies, both within their organisations and in the overall sporting context. Global Sport Leaders will be of interest to students and scholars across a range of disciplines including sports management, sociology, politics, history and international relations. .